Agriculture Technology Acquisition, Development and Dissemination in the Private Sector - Saturnina C. Halos (Philippine Institute for Development Studies (PIDS), 1999)
The study attempts to characterize agricultural technology, acquisition, development and dissemination in the private sector. Technologies extensively used in agriculture are introduced either through established subsidiaries of multinational companies, joint venture agreements, technology transfer tie-ups or outright sale. The purpose of research and development, being market-driven, is the fine-tuning of the imported technology to suit local conditions in terms of technological efficiency, affordability and cultural acceptance. In reality, however, most firms do not maintain a separate research and development unit and most often the marketing and operations staff double as researchers. In addition, research and development are seldom undertaken to locally develop new techniques. In this paper, the contrast in the approach of developing and managing research and development agenda by the coconut and sugar research foundation is examined. Results imply a significant difference between the two foundations in terms of technological acquisition, development and management.
Keywords: 330; patent and license; agricultural technology